Estrogen receptor- mediates human multidrug resistance associated protein 3 induction by 17-ethynylestradiol. Role of activator protein-1 - Ruiz, Maria Laura (2013)
Previously, we have demonstrated that 17α-ethynylestradiol (EE) induces rat multidrug-resistance associated protein 3 (Mrp3, Abcc3) expression transcriptionally through estrogen receptor-α (ER-α) activation. We explored the effect of EE on MRP3 expression of human origin. HepG2 cells were transfected with ER-α and incubated with EE (1–10–50 μM) for 48 h. MRP3 protein and mRNA levels were measured by Western blotting and Real time PCR, respectively. EE up-regulated MRP3 protein and mRNA at 50 μM only in ER-α(+)-HepG2 cells. The in silico analysis of mrp3 promoter region demonstrated absence of estrogen response elements, but showed several Ap-1 binding sites. We further evaluated the potential involvement of the transcription factors c-JUN and c-FOS (members of Ap-1) in MRP3 up-regulation. ER-α(+) HepG2 cells were incubated with EE and c-FOS and c-JUN levels measured by Western blotting in nuclear extracts. EE up-regulated only c-JUN. Experiments of overexpression and knock-down of c-JUN by siRNA further demonstrated that this transcription factor is indeed implicated in MRP3 upregulation by EE. Co-immunoprecipitation assay demonstrated that EE induces c-JUN/ER-α interaction, and chromatin immunoprecipitation assay showed that this complex is recruited to the AP-1 binding consensus element present at the position (−1300/−1078 bp) of human mrp3 promoter. We conclude that EE induces MRP3 expression through ER-α, with recruitment of ER-α in complex with c-JUN to the human mrp3 promoter.